Application of Self-Instruction Techniques to Reduce Student Bullying Behavior - Juta, Sandra Fatmala; Aryani, Farida; Umar, Nur Fadhilah (Indonesian Journal of Educational Studies, 2024)
This research examines the influence of applying self-instruction techniques to reduce student bullying behavior at SMPN 7 Anggeraja. The issues addressed in this study are: (1) What is the description of bullying behavior exhibited by subjects at SMPN 7 Anggeraja? (2) What is the description of the application of self-instruction techniques to reduce bullying behavior by subjects at SMPN 7 Anggeraja? (3) How can self-instruction techniques reduce bullying behavior among student subjects at SMPN 7 Anggeraja? The research objectives are: (1) To understand the description of bullying behavior exhibited by subjects at SMPN 7 Anggeraja. (2) To understand the description of the application of self-instruction techniques in reducing bullying behavior by subjects at SMPN 7 Anggeraja. (3) To understand the influence of self-instruction techniques in reducing bullying behavior among student subjects at SMPN 7 Anggeraja. This research method applies a quantitative approach using the single-subject research method and employs an A-B-A design. The research subjects consist of two ninth-grade students with high levels of bullying behavior. Data processing is conducted through descriptive and visual analysis. The research findings reveal that: (1) The level of bullying behavior before treatment was high. (2) Self-instruction techniques were conducted over four sessions, with high student participation levels during the research implementation. (3) The application of self-instruction techniques successfully reduced bullying behavior among students at SMPN 7 Anggeraja.